Immune effectors responsible for the elimination of hyperploid cancer cells. (3rd August 2018) - Aranda, Fernando; Chaba, Kariman; Bloy, Norma; Garcia, Pauline; Bordenave, Chloé; Martins, Isabelle; Stoll, Gautier; Tesniere, Antoine; Kroemer, Guido; Senovilla, Laura
ABSTRACT: The immune system avoids oncogenesis and slows down tumor progression through a mechanism called immunosurveillance. Nevertheless, some malignant cells manage to escape from immune control and form clinically detectable tumors. Tetraploidy, which consists in the intrinsically unstable duplication of the genome, is considered as a (pre)-cancerous event that can result in aneuploidy and contribute to oncogenesis. We previously described the fact that tetraploid cells can be eliminated by the immune system. Here, we investigate the role of different innate and acquired immune effectors by inoculating hyperploid cancer cells into wild type or mice bearing different immunodeficient genotypes ( Cd1d −/−, FcRn −/−, Flt3l −/−, Foxn1 nu/nu, MyD88 −/−, Nlrp3 − / −, Ighm tm1Cgn, Rag2 −/− ), followed by the monitoring of tumor incidence, growth and final ploidy status. Our results suggest that multiple different immune effectors including B, NK, NKT and T cells, as well as innate immune responses involving the interleukine-1 receptor and the Toll-like receptor systems participate to the immunoselection against hyperploid cells. Hence, optimal anticancer immunosurveillance likely involves the contribution of multiple arms of the immune system.